DIGITAL MARKETING STRATEGIES BASED ON LIVE STREAMING AND AI RECOMMENDATION IN ENHANCING CONSUMER TRUST IN CULINARY MSMEs - Diah Pradiatiningtyas; Lina Ayu Safitri; Chriswardana Bayu Dewa (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
The development of digital marketing has encouraged Micro, Small, and Medium Enterprises (MSMEs) to utilize social media, live streaming, and Artificial Intelligence (AI) technologies to improve consumer interaction. Previous studies have primarily focused on the quantitative effectiveness of promotional activities, while in-depth investigations concerning consumer experiences and customer trust toward the combination of live streaming and AI recommendation systems remain limited. This study aims to analyze how digitalmarketing strategies based on live streaming and AI recommendations shape consumer trust, particularly in culinary MSMEs. This research employed a qualitative case study approach. Data were collected through in-depth interviews, social media observations, and digital documentation. Informants consisted of culinary MSME owners, social media administrators, and activeconsumers using TikTok Shop and Instagram Live. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that real-time interactions during live streaming enhance consumers’ emotional closeness, while AI recommendations support promotional personalization and increase purchase interest. The noveltyof this study lies in the integration of live-streaming marketing and AI recommendation systems as a strategy for building customer trust in local culinary MSMEs.